Castle of Courcelles-le-Roy - Beaulieu (45) - C.F.M (Wikimedia Commons, 1930)
Carte postale ancienne issue de Wikimedia Commons. Titre: Castle of Courcelles-le-Roy - Beaulieu (45). BEAULIEU - Château de Courcelles-le-Roi - A t habit par Charles VII et Agns Sorel, colored postcard printed in France by C.F.M.
Droits : Licence Public domain via Wikimedia Commons
Keywords: carte postale; image; Patrimoine; Histoire Locale; Wikimedia Commons; Château; Carte postale